Respuesta :

djb634

Answer:

the answer is c

Step-by-step explanation:


Answer:

c) y−6=−2(x+2)

Step-by-step explanation:

The general point slope form equation is:

y - y1 = m*(x - x1)

where x and y are the variables, (x1, y1) is the coordinate of a point on the line and m is the slope of the line.

To calculate the slope of the line we need two points on the line (x1, y1) and (x2, y2) and the following equation:

m = (y2 - y1)/(x2- x1)

Coordinates of point A: (-2, 6)

Coordinates of point B: (2, -2)

Replacing into the equation:

m = (6 - (-2))/(-2 - 2)

m = 8/(-4)

m = -2

Replacing this value and coordinate of point A into the general point slope equation we get:

y - 6 = -2*(x - (-2))

y - 6 = -2*(x + 2)

ACCESS MORE